Effect of freeze drying on in vitro ruminal fermentation dynamics of three tropical shrub legumes with and without condensed tannins - Tiemann, Tassilo T.; Ávila Vargas, P.; Lascano Aguilar, Carlos Eduardo; Kreuzer, M.; Hess, H.D. (2009)
Extensive comparisons of the effects of tropical shrub legumes rich in condensed tannins (CT) require well-conserved material. It is, however, unclear if the application of even gentle methods like freeze drying (lyophilization) affects the results in comparison to fresh material. Therefore, an experiment with the gas-pressure transducer technique, simulating ruminal fermentation dynamics in vitro, was conducted to investigate the effect of freeze drying on the ruminal nutrient degradability of three tropical multipurpose shrub legumes. Leaves of the CT shrubs Calliandra calothyrsus and Flemingia macrophylla and of the CT-free shrub Cratylia argentea were tested either in fresh form or lyophilized. In order to simulate practical feeding conditions, the legume leaves were incubated together with Brachiaria humidicola (1:2) for 144 h. Additionally, incubations were carried out either with or without polyethylene glycol (PEG) to be able to separate effects either dependent or independent of the CT.